Freedom and Resistance : A Social History of Black Loyalists in the Bahamas - Curry, Christopher, 1971- (Book collections on Project MUSE., 2017)
Christopher Curry recovers a social history of black loyalists in the Bahamas that highlights intra- and inter-racial dynamics and examines their impact on evolving Bahamian society. This volume also examines the racial discord that erupted between black and white loyalists as, respectively, one group sought greater legal freedoms while the other sought greater economic benefits. With this work, Curry adds a new chapter to the global dimensions of the freedom struggle that emanated from the American Revolution.